University graduates' perceptions of institutional hierarchies. The case of Finnish Master's degree in business administration and economics - Isopahkala-Bouret Ulpukka; Kosunen Sonja; Haltia Nina (Routledge, Taylor & Francis Group, 2025)
In the process of higher education choice, the prospective students compare and organise universities into a preference order, which indicates status hierarchies among institutions. In this study, the aim is to investigate how (and based on what) recent business graduates construct institutional hierarchies in the national higher education landscape in Finland. Moreover, we ask how the geographical location of universities contributes to such hierarchies. Based on 43 interviews with Master’s degree graduates from four universities and their satellite campuses, we argue that the long distances between universities in a geographically large country eventually contest the relevance of status comparisons between universities, when it actually comes to making a choice. This does not indicate, however, that institutional hierarchies would not exist nor be of relevance. Our findings reveal that hierarchy is produced through the perceived selectivity of admissions, future exchange value of education, and competitiveness/inclusiveness of student culture.